The HFA‐PEFF score identifies ‘early‐HFpEF’ phenogroups associated with distinct biomarker profiles - Michiel T.H.M. Henkens; Anne‐Mar vanOmmen; Sharon Remmelzwaal; Gideon B. Valstar; Ping Wang; Job A.J. Verdonschot; Mark R. Hazebroek; Leonard Hofstra; Vanessa P.M. vanEmpel; Joline W.J. Beulens; Hester M. denRuijter; Stephane R.B. Heymans (ESC Heart Failure)
Abstract Aims The HFA‐PEFF score was developed to optimize diagnosis and to aid in early recognition of heart failure (HF) with preserved ejection fraction (HFpEF) in patients who present with HF‐like symptoms. Recognizing early‐HFpEF phenogroups is essential to better understand progression towards overt HFpEF and pave the way for early intervention and treatment. Whether the HFA‐PEFF domain scores can identify ‘early‐HFpEF’ phenogroups remains unknown. The aims of this pilot study are to (i) identify distinct phenogroups by cluster analysis of HFA‐PEFF domain scores in subjects that present with HF‐like symptoms and (ii) study whether these phenogroups may be associated with distinct blood proteome profiles. Methods and results Subjects referred to the Cardiology Centers of the Netherlands, location Utrecht, with non‐acute possibly cardiac‐related symptoms (such as dyspnoea or fatigue) were prospectively enrolled in the HELPFul cohort (N = 507) and were included in the current analysis. Inclusion criteria for this study were (i) age ≥ 45 years and (ii) a left ventricular ejection fraction (LVEF) ≥ 50%, in the absence of a history of HF, coronary artery disease, congenital heart disease, or any previous cardiac interventions. Multinominal‐based clustering with latent class model using the HFA‐PEFF domain scores (functional, structural, and biomarker scores) as input was used to detect distinct phenotypic clusters. For each bootstrapping run, the 92 Olink proteins were analysed for their association with the identified phenogroups. Four distinct phenogroups were identified in the current analysis (validated by bootstrapping 1000×): (i) no left ventricular diastolic dysfunction (no LVDD, N = 102); (ii) LVDD with functional left ventricular (LV) abnormalities (N = 204); (iii) LVDD with functional and structural LV abnormalities (N = 204); and (iv) LVDD with functional and structural LV abnormalities and elevated BNP (N = 107). The HFA‐PEFF total score risk categories significantly differed between the phenogroups (P < 0.001), with an increase of the HFA‐PEFF score from Phenogroup 1 to 4 (low/intermediate/high HFA‐PEFF risk score: Phenogroup 1: 88%/12%/0%; Phenogroup 2: 9%/91%/0%; Phenogroup 3: 0%/92%/8%; Phenogroup 4: 5%/83%/12%). Thirty‐two out of the 92 Olink protein biomarkers significantly differed among the phenogroups. The top eight biomarkers—N‐terminal prohormone brain natriuretic peptide, growth differentiation factor‐15, matrix metalloproteinase‐2, osteoprotegerin, tissue inhibitor of metalloproteinase‐4, chitinase‐3‐like protein 1, insulin‐like growth factor‐binding protein 2, and insulin‐like growth factor‐binding protein 7—are mainly involved in inflammation and extracellular matrix remodelling, which are currently proposed key processes in HFpEF pathophysiology. Conclusions This study identified distinct phenogroups by using the HFA‐PEFF domain scores in ambulant subjects referred for HF‐like symptoms. The newly identified phenogroups accompanied by their circulating biomarkers profile might aid in a better understanding of the pathophysiological processes involved during the early stages of the HFpEF syndrome.